Human capital and economic growth nexus: Does corruption matter? - Khalil Mudassaar; Hafeez ur Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This paper investigates the human capital and economic growth nexus in the presence of corruption for a disaggregated sample of developed and developing economies, and East, West, and South Asia. For the purpose, Dynamic Panel Data (DPD) and the Generalized Method of Moments (GMM) are employed. The findings provide inferences that human capital positively affects economic growth even though for some groups of economies, corruption boost up economic growth while for some others, it retards the economic growth. The results also suggest that an augmented Solow production function is best fitted to the data. The population growth rate negatively affects economic growth for all economies, but democracy has mixed effects for the groups of the economies.
Keywords: 330; corruption; human capital; democracy; population growth; economic growth